2011
DOI: 10.3389/fmicb.2011.00110
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide Emissions from Ephemeral Wetland Soils are Correlated with Microbial Community Composition

Abstract: Nitrous oxide (N2O) is a greenhouse gas with a global warming potential far exceeding that of CO2. Soil N2O emissions are a product of two microbially mediated processes: nitrification and denitrification. Understanding the effects of landscape on microbial communities, and the subsequent influences of microbial abundance and composition on the processes of nitrification and denitrification are key to predicting future N2O emissions. The objective of this study was to examine microbial abundance and community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
(79 reference statements)
2
9
0
Order By: Relevance
“…Although soil pH has a significant impact on denitrifiers in temperate soils , data suggest that the low nitrate content of the vegetated unturbated peat soil and the dissimilar denitrifier communities rather than soil pH might account for the contrasting N 2 O emission patterns of cryoturbated and unturbated peat soils (Figure 1; Repo et al, 2009, Marushchak et al, 2011. The contrasting denitrifier communites of such soils reacted differently to nitrate and nitrite supplementations (Figures 1b and 2, and Supplementary Figure S2), lending further support to the hypothesis that denitrifier community composition impacts regulation and thus prediction of N 2 O fluxes (Holtan-Hartwig et al, 2000;Philippot et al, 2009Philippot et al, , 2011Ma et al, 2011).…”
Section: Discussionsupporting
confidence: 57%
“…Although soil pH has a significant impact on denitrifiers in temperate soils , data suggest that the low nitrate content of the vegetated unturbated peat soil and the dissimilar denitrifier communities rather than soil pH might account for the contrasting N 2 O emission patterns of cryoturbated and unturbated peat soils (Figure 1; Repo et al, 2009, Marushchak et al, 2011. The contrasting denitrifier communites of such soils reacted differently to nitrate and nitrite supplementations (Figures 1b and 2, and Supplementary Figure S2), lending further support to the hypothesis that denitrifier community composition impacts regulation and thus prediction of N 2 O fluxes (Holtan-Hartwig et al, 2000;Philippot et al, 2009Philippot et al, , 2011Ma et al, 2011).…”
Section: Discussionsupporting
confidence: 57%
“…Others have also found that these groups differ in their distribution pattern in Cryosols, although these other reports were in glacier forefield soils which are considerably harsher environments than the one's studied here (Kandeler et al ., 2006; Brankatschk et al ., 2011). The nosZ primers selected in this study have been successfully used to examine nosZ communities in many soil microbiological studies (Rösch et al ., 2002; Rich et al ., 2003; Liu et al ., 2010; Ma et al ., 2011). However, the nosZ amplicons (700 bp) generated by these primers are longer than 500 bp and may not be ideal for qPCR work.…”
Section: Discussionmentioning
confidence: 99%
“…The assay is designed to measure the overall denitrification potential (DEA) and net N 2 O formation (N 2 Of) in soil by alleviating environmental constraints (Cavigelli and Robertson, 2000; Ma et al ., 2011). The DEA and N 2 Of were measured according to Ma and colleagues (2011). Briefly, soil slurries were prepared in a 70 ml crimp‐sealed serum bottle by mixing 10 g soil and 10 ml of a test solution containing 10 mM glucose, and 5 mM KNO 3 .…”
Section: Methodsmentioning
confidence: 99%
“…N 2 O decreasing was also associated with the abundance of 16:1x9 fatty acid; the intensification of consumption of N 2 O during flooding was in fact statistically coupled with the increase in the presence of 16:1x9 fatty acid, the metabolic precursor of cyclopropane fatty acid (cy17:0) that mainly occurs in Gram-negative bacteria, including denitrifying bacteria (Jantzen 1984;Grogan and Cronan 1997). Although denitrification is generally more related to changes in soil environmental conditions (Attard et al 2011), Ma et al (2011, by studying microbial abundance and community composition in relation to N 2 O associated with the denitrification process in soils from cultivated and uncultivated wetlands, found that changes in the denitrifier nitrous oxide reductase gene (nosZ) abundance and community composition were good predictors of net soil N 2 O emissions.…”
Section: Discussionmentioning
confidence: 99%